Dialogue in the Educational Process: Building Community - Síveres, Luiz (Journal of ecumenical studies, 2022)
Understanding dialogue from the perspective of education in the current context requires a perception of reality that is revealed with a marked tendency for personal egocentrism, social inequality, and religious proselytism. This can be perceived by different experiences that reveal, in part, an individual encapsulation, a political polarization, and a religious division—aspects that express the need to promote dialogue between and among people, social groups, and religious denominations. Hence, it is proposed to return to the concept and practice of dialogue based on a relational dynamic, guided by the proposal of Martin Buber. To illuminate social reality, the theory of Jürgen Habermas will be revisited, and, to deepen the disposition of the dialogue with the purpose of building an educational project, the suggestion of Hans Küng will be accepted. Such assumptions, among others, are recognized as elements of an educational project in which dialogue should be exercised as a lifestyle, a way of living, and a possibility to transcend—through the experience of significant relationships, promotion of social equality, or universal communal experience.